2018
DOI: 10.1111/cbdd.13314
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy studies of Sclerotium rolfsii lectin on breast cancer using NOD SCID mouse model

Abstract: Expression of altered glycans such as TF, Tn, and sTn antigens has been observed in a number of carcinomas which are targeted in cancer therapy. Sclerotium rolfsii lectin (SRL) is known to recognize TF and its substituted forms. Clinical potential of SRL has been demonstrated by studying its interaction with different types of cancer cells. Here we report, in vitro studies of SRL on breast cancer MDA-MB-468 cells and in vivo studies with MCF-7 xenografts. In vitro growth inhibitory studies of SRL on metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…With increased concentration or exposure time, the antiproliferative activity is also increased (De Mejía & Prisecaru, 2005;Valadez-Vega et al, 2011). Several plant lectins retained cytotoxic effects against different cancer cell lines and caused cell death in vitro and in vivo (Anupama et al, 2017;Hasan et al, 2019;Hegde et al, 2018;Nascimento et al, 2019) without causing toxicity in normal cells (Fik et al, 2001). EAC cells are considered as a suitable model cell line for anticancer drug test because of the absence of H-2 histocompatibility antigens (Chen & Watkins, 1970), which may be the ground behind their accelerated proliferation and made them studying in almost every mouse host.…”
Section: Discussionmentioning
confidence: 99%
“…With increased concentration or exposure time, the antiproliferative activity is also increased (De Mejía & Prisecaru, 2005;Valadez-Vega et al, 2011). Several plant lectins retained cytotoxic effects against different cancer cell lines and caused cell death in vitro and in vivo (Anupama et al, 2017;Hasan et al, 2019;Hegde et al, 2018;Nascimento et al, 2019) without causing toxicity in normal cells (Fik et al, 2001). EAC cells are considered as a suitable model cell line for anticancer drug test because of the absence of H-2 histocompatibility antigens (Chen & Watkins, 1970), which may be the ground behind their accelerated proliferation and made them studying in almost every mouse host.…”
Section: Discussionmentioning
confidence: 99%
“…For the betterment of cancer patients, research has been going on to find an alternative mode of action for treatment than chemotherapy and chemoprevention. In this regard, SRL has shown many properties that can be useful in combating tumor cells [142]. In many cancer therapies, we observe that along with tumor cell destruction, some normal cells are also affected which might be detrimental to the patients body.…”
Section: Lectins As Diagnostic and Therapeutic Agentsmentioning
confidence: 85%
“…On a mice model that had MCF-7xenografts, SRL efficacy was observed. It was found that SRL was inhibiting tumor proliferation [142]. (4) Helix pomatia: Helix pomatia agglutinin (HPA) obtained from the Roman snails is part of the carbohydrate-binding protein family.…”
Section: Lectins As Diagnostic and Therapeutic Agentsmentioning
confidence: 99%
“…The current literature reports on the application of lectins of several origins in cancer models, namely of animal lectins [30][31][32] , microorganisms lectins [33,34], and, most of all, plant lectins. This review aims to highlight these studies with particular focus on plant lectins applied on the recognition of BCa glycans, as well as their cytotoxic/antiproliferative effects.…”
Section: Introductionmentioning
confidence: 99%